A Point of Care Quality Improvement Initiative for Enhancing Immediate Drying of Babies and Prevention of Hypothermia in Labor Room, Nishtar Medical University, Multan Pakistan - Asma Akhter, Humaira Bashir, Summaira Perveen, Sajilah Karim, Ayesha Khan Khakwani, Mirab Badar, Huma Quddussi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the current status of prevention of neonatal hypothermia by firstly, initialization of immediate drying and skin to skin contact of all newborns delivered by spontaneous vaginal delivery, and secondly, to initiate early breast feeding. Methodology: This was an observational study carried out in labor room of Gyne Unit 1, Nishtar Medical University (NMU) and Hospital, Multan Pakistan from April to September 2019. Based on “Point of Care Quality Improvement (POCQI)” guidelines, Initially, data were collected for 4 weeks during morning shift (phase 1) utilizing 2 indicators i-e immediate drying and number of babies who developed hypothermia within one hour of birth. Data were analyzed; results interpreted, and necessary modifications made. After implementation of changes further data was collected for 24 hours shift of gyne unit 1 for the rest of study period including additional indicators i.e., initiation of early breastfeeding and skin to skin contact. Results: A total of 744 babies delivered over a period of six months during this initiative, which was carried out in 2 phases, the phase-1 comprised of four weeks and included study of 24 babies and the phase 2 included 720 babies over five months. During phase-1, all 24 (100%) newborns were dried immediately after birth and the temperature was recorded among 20 (83.3%) of the babies with lost to follow up of 4 (16.7%) babies due to shifting to NICU for intensive care. During the second phase, among 720 babies that were delivered, 590 (81.9%) received skin-to-skin care for minimum of half hour due to rapid turnover of patients for delivery in labor room. Breastfeeding was initiated within one hour after birth in 593 babies (82.3%). Temperature was recorded among 528 (73.3%) babies with 37 (5.1%) shifted to NICU. Hypothermia was observed in 10 babies (1.4%) during this phase. Practical Implications: Hypothermia is a preventable cause of neonatal mortality which can be easily prevented by training of health care providers, midwives, and lady health visitors to incorporate components of essential newborn care in their medical practice. Conclusion: Implementation of POQCI was found to be highly applicable yielding good response. Keywords: Newborn, hypothermia, immediate drying, point of care quality improvement, neonatal intensive care unit.